2016
DOI: 10.1590/1413-70542016402039115
|View full text |Cite
|
Sign up to set email alerts
|

Determination of cardinal temperatures for sugar apple ( Annona squamosa L.)

Abstract: The sugar apple is highly dependent on the pollination and fruit tree pollen performance is crucial for successful fertilization and fruit set. The objective of this study was to determine the cardinal temperatures for in vitro pollen grains germination and evaluate the effect of temperature on pollen tube growth of sugar apple. The experimental design was in a completely randomized with eight treatments (10, 15, 20, 25, 30, 35, 40 and 45 ºC), four replicates and each plot was constituted by two slides per pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…and the viability of the pollen grains of the sugar apple trees that is higher to that of atemoya (Nietsche et al, 2009;Rodrigues et al, 2016).…”
Section: /10mentioning
confidence: 89%
“…and the viability of the pollen grains of the sugar apple trees that is higher to that of atemoya (Nietsche et al, 2009;Rodrigues et al, 2016).…”
Section: /10mentioning
confidence: 89%
“…Second, the problem of inefficient pollination is due to high temperatures (30°C) and low relative humidity (30%), while low temperature (25°C) and high relative humidity (80%) enable efficient pollination (Khalate, Supe, & Doke, 2018). Rodrigues et al (2016) studying different temperatures for the in vitro pollen grain germination of A. squamosa, found that the temperature of 25 ± 1°C provided the best in vitro germination, with 48.13%, and as the temperature increased, germination percentage decreased significantly. George and Nissen (1988) cite that high temperatures adversely affect flower bud production, suggesting that tropical conditions are not conducive to high sugar-apple yields.…”
Section: Introductionmentioning
confidence: 99%